USSR IN REPORTS OF ITALIAN DIPLOMATS (1924-1941) - O. V. Dubrovina (MGIMO University Press, 2016)
In this article the reports of Italian diplomatic officials who worked in the USSR between the two World Wars will be analyzed. On the basis of the unpublished sources, an attempt to explain Mussolini's decision to enter the war against the USSR in 1941 will be carried out. As a historical source, the diplomatic reports present, on one hand, rich material about different aspects of soviet life as seen by foreigners and presented by them with thorough details. On the other hand, the subjective character of the diplomatic information foresees a critical approach towards the judgements and opinions of Italian diplomats. However, despite the limitation of their sources from where the Italian diplomats obtained the information, we have to underline the importance of the diplomatic reports and to consider the diplomatic channel as one of the multiple factors in the determining process of the international fascist policy. The attention is focused on two aspects of soviet reality: public sentiment and the national mentality of Russian people. The goal of the article is to examine the mechanism that led to the diplomats' conclusions about the soviet power instability and about its imminent collapse in the case of foreign invasion.